Постструктуралистский взгляд на развитие медиакультуры - Кухарец, Т. И. (ХНУРЭ, 2012)
The present report concerns different philosophical ways of understanding modern mediaculture. The author emphasizes the role of philosopherspoststructuralists in development of this conception and resumes their opinions in his own way.